Arba’īn and Bakhshū’s Lament: African Slavery in the Persian Gulf and the Violence of Cultural Form - Parisa Vaziri (Antropologia)
Arba’īn names the Shi’a elegiac ritual commemorating the fortieth day of ‘Āshūrā – the 7th century murder of Husayn at the Battle of Karbala. In South Iranian provinces like Būshihr Arba’īn expresses a distinctly black character marked by animation and drumming virtuosity. Iranian filmmaker Nāsir Taqvāī’s experimental ethnographic documentary Arba’īn (1970) chronicles the regional peculiarities of this ritual, reflecting in both its form and content fragile testament to a haphazardly recorded history of African slavery absorbed into oblivion. Drawing upon historiographical, musicological, ethnographic sources and black studies, this article takes Taqvā’ī’s filmic mediation as an occasion to demonstrate the way so-called syncretized forms reveal historical information about slavery in nontransparent ways.